Pengembangan Bahan Ajar Digital Teks Cerita Fantasi Bermuatan Karakter bagi Siswa Kelas VII Smp - Iis Jubaedah; Abdul Rozak; Yusida Gloriani (IKIP PGRI Bojonegoro, 2023)
Abstract: The background in this research is because of the importance of instilling character education in learning and the use of digital teaching materials that are still rarely used. There is no alternative media for textbooks as a learning resource for students to learn Indonesian, especially fantasy story text material. This study aims to explain the development of digital fantasy story text teaching materials that include character values in learning fantasy story texts for seventh grade junior high school students. This type of research uses the ADDIE development method which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were seventh grade students of SMP Negeri 1 Jalaksana and SMP Islam Terpadu Al-Multazam 2. The results obtained from the analysis of the average teacher needs of 92% strongly agreed about the need for digital teaching materials to instill character values through story text learning. fantasy and 100% requires digital media materials in learning Indonesian, especially fantasy story texts. Analysis of student needs 87% of students said they wanted media containing images, animation, video, and sound and 81% of students agreed when studying in the laboratory using a laptop/computer with digital learning media. For the feasibility of digital teaching materials, the material expert score is 2900 points, media expert is 2640 points, graphic design expert is 1800, practitioners are 2340 points, the Indonesian language teacher response test is 30620 points with a total overall score of three experts and practitioners getting 40300 points, with a percentage score of 86.11 included in the very good criteria. These results indicate that the learning media for developing digital teaching materials for fantasy story texts containing character education for class VII is in the